Evaluation of Stable Pigment Extracted from Red Tomato (Solanum lycopersicon) - Nurul Aida binti Abdul Mukti; Shakila binti Abdullah (Enhanced Knowledge in Sciences and Technology, 2021)
Lycopene is a bright red carotenoid pigment and a phytochemical compound that can be discovered in the tomatoes. The aim of this study is to produce the stable colouring towards temperature and pH by using suitable method of extraction and its potential to be alternative natural food colourant. The lycopene pigment was detected at wavelength 470 and 471 nm by using UV-Vis spectroscopy analysis. In this study, the lycopene was extracted from red tomato (Solanum lycopersicon) by using hexane and acetone as the solvent. The maceration method has been applied in order to maintain the stability of the pigment where 173.88 mg/kg tomato pomace obtained from this study. Lycopene pigment was instable at alkaline medium and at temperature 50 and 60 °C where the great loss of this pigment is noticed at both parameters. Meanwhile, the antioxidant activities (66.35 %) and antimicrobial properties towards gram-positive bacteria were confirmed to be present inside the lycopene pigment. Keywords: Lycopene, Extraction, Stability, Antioxidant, Antimicrobial.